Successful strategies that address gender-related barriers and promote bodily autonomy within efforts to scale up and sustain postpregnancy contraception: a scoping review - James Kiarie; Rita Kabra; Anna Coates; Arachu Castro (BMJ Global Health)
Introduction Acknowledging the integral role of bodily autonomy in advancing gender equality, our study aimed to assess the extent to which strategies used in postpartum and postabortion contraception have effectively equipped women, girls and gender-diverse individuals with the tools, knowledge and resources required to make autonomous decisions that align with their diverse life experiences.Methods We conducted a scoping review using the databases PubMed, EBSCOhost, EMBASE and SciSpace. We included implementation, evaluation and experimental studies published in any language between 2013 and 2023 and excluded studies not meeting these criteria. We used a WHO scale to determine the level of gender responsiveness.Results We found 30 implementation, evaluation and experimental studies published in any language between 2013 and 2023. We categorised the strategies following the WHO scale as gender-transformative (4 studies), gender-specific (24 studies) and gender-sensitive (2 studies). None of the studies reported strategies hindering reproductive health and rights. All strategies involved women and girls, and none explicitly targeted gender-diverse people capable of childbearing.Conclusions This study highlights the importance of integrating gender-transformative activities into postpregnancy contraceptive strategies and underscores the necessity of understanding and addressing local gender norms and the broader health system context to promote bodily autonomy effectively. The findings suggest that success should not be solely measured by contraceptive uptake but also by how well interventions address gender-related barriers.